Finding the largest volume and surface objects using a Lagrange function (Texas Journal of Multidisciplinary Studies, 2021)
It is easy to find the extrema of functions of many variables. This thesis explores the properties of the largest surface and volume forms that are useful in optimization problems using the conditional extremum of multivariate functions.